The Influence of Product Quality on Customer Loyalty Mediated by Customer Satisfaction in Scarlett Whitening Serum Products in Bandung City - Sarah Rahmawati; Vita Dhameria (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2025)
This study aims to examine the effect of product quality on customer loyalty with customer satisfaction as a mediating variable among users of Scarlett Whitening serum in Bandung City. This study uses a quantitative approach as the research method, analyzed using simple regression, multiple regression, and the Sobel test through SPSS. The results show that product quality has a significant influence on customer satisfaction and customer loyalty. Customer satisfaction also has a strong positive effect on loyalty and mediates the relationship between product quality and customer loyalty. These findings indicate that high product quality enhances satisfaction, which in turn strengthens customer loyalty. This study contributes to the literature by emphasizing the mediating role of satisfaction in the relationship between perceived product quality and customer loyalty in the skincare industry. To increase customer retention, Scarlett Whitening is recommended to maintain product efficacy, enhance user experience, and utilize customer satisfaction testimonials in marketing strategies.